2017
DOI: 10.18632/oncotarget.17031
|View full text |Cite
|
Sign up to set email alerts
|

OVOL2 antagonizes TGF-β signaling to regulate epithelial to mesenchymal transition during mammary tumor metastasis

Abstract: Great progress has been achieved in the study of the role of TGF-β signaling in triggering epithelial-mesenchymal transition (EMT) in a variety of cancers; however, the regulation of TGF-β signaling during EMT in mammary tumor metastasis has not been completely defined. In the present study, we demonstrated that OVOL2, a zinc finger transcription factor, inhibits TGF-β signaling-induced EMT in mouse and human mammary tumor cells, as well as in mouse tumor models. Data from the Oncomine databases indicated a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 50 publications
(59 reference statements)
1
41
0
Order By: Relevance
“…The dysregulation of EMT-related TFs has been implicated in cancer progression. The role of OVOL2, an EMT-repressing TF, in suppressing metastasis has been shown in several human cancers, such as breast cancer, colorectal cancer and lung cancer 26 , 27 , 29 , 30 , 36 . In this report, by studying subclonal populations derived from the typical NPC cell line CNE2 that display relatively stable and contrasting phenotypes (S26: epithelial; S18: mesenchymal), we found that OVOL2 was the most significantly changed EMT-TF between the two subclones ( Figure 1 ), and functional analysis suggested that OVOL2 acts not only as a suppressor of metastasis (Figure 3 ) but also as a potent tumor suppressor ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dysregulation of EMT-related TFs has been implicated in cancer progression. The role of OVOL2, an EMT-repressing TF, in suppressing metastasis has been shown in several human cancers, such as breast cancer, colorectal cancer and lung cancer 26 , 27 , 29 , 30 , 36 . In this report, by studying subclonal populations derived from the typical NPC cell line CNE2 that display relatively stable and contrasting phenotypes (S26: epithelial; S18: mesenchymal), we found that OVOL2 was the most significantly changed EMT-TF between the two subclones ( Figure 1 ), and functional analysis suggested that OVOL2 acts not only as a suppressor of metastasis (Figure 3 ) but also as a potent tumor suppressor ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…OVOL2 is an evolutionarily conserved protein that is involved in many important physiological processes, such as oogenesis in drosophila and mice 20 , 21 , cranial neural tube development 22 , mammary morphogenesis 23 , angiogenesis, heart formation and placental development 24 in mice, and ectoderm differentiation in human cells 25 through EMT regulation. Down-regulation of OVOL2 has been found in a variety of cancers, and OVOL2 was reported to inhibit EMT and metastasis by suppressing ZEB1 in breast cancer 26 , TWIST in lung cancer 27 , c-Myc in cutaneous squamous cell carcinoma 28 , Wnt signaling in colorectal cancer 29 and TGF-β signaling in breast cancer 30 .…”
Section: Introductionmentioning
confidence: 99%
“…R-SMADs (SMAD2 and 3) bind to the Co-SMAD, SMAD4, to form complexes that modulate downstream gene expression in the nucleus (33). Previous studies have uncovered a connection between canonical SMAD4 signaling and EMT (34,35). Therefore, it is necessary to test the role of SMAD4 in EMT in renal carcinoma.…”
Section: Smad4 Expression Tif1-γ Expression -------------------------mentioning
confidence: 99%
“…The activity of OvoL might help stabilizing a hybrid E/M phenotype 21, 25 , providing many advantages for both tumors and normal stem cells 28 . Indeed, recent data show that, like adult somatic stem cells, the most aggressive tumors often display a hybrid phenotype between mesenchymal and epithelial states 27 , and the expression of specific OvoL isoforms can annihilate the metastatic potential of mammary tumors 29,19 . In addition, OvoL/Svb factors have been linked to the control of various progenitors/stem cells, from basal invertebrates 30 to mammals 3133 .…”
Section: Figurementioning
confidence: 99%